Experimental Study on the Ice Resistance of a Naval Surface Ship with a Non-Icebreaking Bow - Jianqiao Sun; Yan Huang (Journal of Marine Science and Engineering, 2023)
With the shrinking of Arctic sea ice due to global climate change, potential access to Arctic waters has increased for non-typical icebreaking or strengthened ships. Numerous studies have been conducted on hull form designs and ice resistance predictions for ships with typical icebreaking bows, but published research for ships with non-icebreaking bows in ice is still rare. The objective of this study was to investigate the ice resistance of a naval surface ship with a non-icebreaking bow through model tests in an ice tank. The naval surface combatant concept DTMB 5415 was used as the ship model. The tests were conducted under different levels of ice thicknesses and speeds. During the tests, the total resistance of the model ship was measured, accompanied by monitoring of the ice load at the stem area with a flexible tactile sensor sheet. Compared with the test results of icebreaker models in former studies, the total ice resistance, as well as the stem ice load, of the present ship was significantly higher. The ice crushing resistance component in the stem area accounted for more than 60% of the total resistance in the ice. Discussions on the applicability of a semi-empirical formula for predicting the ice resistance of the present ship are also presented. Keinonen’s formula was found to be relatively more consistent with the predictions produced by model tests, and a preliminary modification was proposed to obtain more accurate predictions.